Mixed disulfides of acyl carrier protein and coenzyme A with specific soluble proteins in Escherichia coli. - Rock, C O (American Society for Microbiology (ASM), 1982)
Three soluble proteins in Escherichia coli specifically from mixed disulfides with either acyl carrier protein or coenzyme A. Coenzyme A was attached to one of these proteins, and the amount bound depended on the cellular coenzyme A concentration. The other two proteins were mixed disulfides between acyl carrier protein and each of the two 3-ketoacyl-acyl carrier protein synthases. IMAGES: